SISTEM PENDUKUNG KEPUTUSAN KEBERLANJUTAN BEASISWA STMIK PELITA NUSANTARA SETIAP SEMESTER DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Nera Mayana Br Tarigan (Lambung Mangkurat University, 2021)
Evaluation in each program is very much needed, as is the case in providing scholarships to students and is a continuous scholarship every semester. In evaluating scholarship recipients, several aspects/criteria are needed. STMIK Pelita Nusantara in helping students who are academically capable and economically disadvantaged provides tuition scholarships in the amount of 25%, 40%, 50%, 75%, and 100%, but in the evaluation every semester the management is less thorough so that the evaluation of scholarship recipients for the sustainability of the scholarship every semester is constrained and seems to let the student just accept the scholarship without evaluation. To overcome this problem, a decision support system is needed by applying the Simple Additive Weighting (SAW) method. The research stages start from identifying problems, collecting data in the form of scholarship recipients' data, criteria data, analyzing using the Simple Additive Weighting method. Designing and building systems, testing systems, compiling reports, and publishing accredited national journals. The research concludes that the Simple Additive Weighting (SAW) method can be applied to analyze the sustainability of the STMIK Pelita Nusantara scholarship every semester in helping the management. With the results of the analysis that it was stated that one person was declared not to be a scholarship on behalf of Priti NIM 200121202 students with a total score of 29.03 and three people were declared to continue the scholarship status on behalf of Harpingka Fitria Br Sibarani NIM 190131108 with a total score of 65.55, Sethu Ramen NIM 200131035 with a total score of 50.97, Monalisa Hotmauli Silalahi NIM 200121197 with a total score of 78.88, Beby Audry NIM 200121198 with a total score of 72.08.Keywords: DSS, SAW method, scholarship sustainability Evaluasi dalam setiap program sangat dibutuhkan, sama halnya dalam pemberian beasiswa kepada mahasiswa dan bersifat beasiswa berkelanjutan setiap semesternya. Dalam evaluasi penerima keberlanjutan beasiswa sangat dibutuhkan beberapa aspek/kriteria. STMIK Pelita Nusantara dalam membantu mahasiswa yang mampu dalam akademik dan kurang mampu secara ekonomi memberikan beasiswa uang kuliah dengan besaran 25%, 40%, 50%, 75% dan 100%, namun dalam evaluasi setiap semesternya manajemen kurang teliti sehingga evaluasi terhadap penerima beasiswa untuk keberlanjutan beasiswa setiap semester terkendala dan seakan membiarkan begitu saja mahasiswa tersebut menerima beasiswa tanpa evaluasi. Untuk mengatasi masalah tersebut maka sangat dibutuhkan suatu system pendukung keputusan dengan menerapkan metodr Simple Additive Weighting (SAW). Tahapan penelitian mulai dari mengidentifikasi masalah, pengumpulan data berupa data-data mahasiswa penerima beasiswa, data kriteria, menganalisa dengan metode Simple Additive Weighting. Perancangan dan membangun sistem, pengujian sistem, penyusunan laporan dan publikasi jurnal nasional terakreditasi. Kesimpulan hasil penelitian bahwa metode Simple Additive Weighting (SAW) dapat diterapkan untuk menganalisa keberlanjutan beasiswa STMIK Pelita Nusantara setiap semester dalam membantu pihak manajemen. Dengan hasil analisa bahwa dinyatakan satu orang menjadi tidak beasiswa atas nama mahasiswa Priti NIM 200121202 dengan total nilai 29,03 dan tiga orang dinyatakan tetap melanjut status beasiswa atas nama Harpingka Fitria Br Sibarani NIM 190131108 dengan total nilai 65,55, Sethu Ramen NIM 200131035 dengan total nilai 50,97, Monalisa Hotmauli Silalahi NIM 200121197 dengan total nilai 78,88, Beby Audry NIM 200121198 dengan total nilai 72,08.Kata kunci: DSS, metode SAW, keberlanjutan beasiswa